Centralization of Pediatric Surgery in The Netherlands - Wijnen, Marc HWA (European Journal of Pediatric Surgery, 2017)
In this article, the route to centralization of rare congenital surgical diseases in the Netherlands is described. The pros and cons are addressed and the point of view of the Netherlands Society for Pediatric Surgery is explained.
Keywords: centralization; pediatric surgery; neonatal surgery